Questions of Information Security in the National Strategy of Russia and Kazakhstan - A. A. Kovalev (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
In the article the major aspects of the problem of information security in the national strategy of Russia and Kazakhstan which are connected by community of historical destiny and denial of basic principles of democracy of the western sample are considered. The logic of geopolitical processes during an era of civilization opposition will lead, according to the author, to association of these countries in uniform Eurasian community. Problems of information security of the Russian Federation and Kazakhstan organically enters their national strategy and depend on efficiency of information policy which is, on the bigger measure dependent on the government device. But without skillful and effective information policy the efficiency of the Eurasian conglomerate will be insignificant.